Pemberdayaan Ekonomi Komunitas Muslim Melalui Bank Sampah: Studi Kasus Majlis Talim Alkaromah Kelurahan Pejuang Kecamatan Medan Satria Bekasi - Rihlah Nur Aulia; Izzatul Mardhiah; Sari Narulita; Nur Amanah (Islamic Religious Education Departement, 2015)
This research is motivated by the empowerment of Muslim community through majlis talim or recitation group of mothers in the field of religion and social empowerment of society and its member economics in solving the environmental problems and protection of nature and natural resources can not be solved only by relying on knowledge and technology. Environmental problems and crises can only be overcome by fundamental and radically changing the way people view and behave towards their natural environment. What is needed is a change of perspective and behavior that is not only an individual, but it must be a culture of society at large. The main purpose of this study is to find out how the model of empowerment of Muslim community conducted by the group of majlis talim alkaromah dikelurahan Pejuang sub district Medan satria Bekasi. This research uses qualitative approach. This research is a kind of qualitative research that is through library research which is kind of research from literature treasury and make text world as the main object of analysis, that is by writing, identifying, clarifying, reducing, and presenting data obtained from written source. This study concludes: First, the model of economic empowerment of Muslim society conducted by majlis talim mothers through Garbage Bank can improve the economics of the members of majlis alkaromah. Second, in Bank garbage majlis talim alkaromah aims to empower and can make society more independent. Such programs save the waste which is then converted to rupiah, then with managing the waste, the sharing of profits with the profit-sharing system, and there is also a group of joint ventures through cooperatives, with this joint effort can improve the skills and independence of the community so that when the community Islam is independent, the empowerment has been successful.